EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN KOPI DAN KARET DI DAERAH ALIRAN SUNGAI JAMBANGAN KABUPATEN KARANGANYAR TAHUN 2011 - Setiawan, Eri (Pendidikan Geografi, 2013)
ABSTRACTThe research is aimed to : (1) to know sub-class level of actual land suitability for coffee and rubber plant, (2) know sub-class of potential land suitability for coffee and rubber plant, and (3) know coffee and rubber productivity at Jambangan Watersheed in Karanganyar Regency.Based on the result of the research it can concluded as follows: (1) there are 9 subclass actual land suitability for coffe plant, those are : S2 w,r,f,n,s/m,e (0,51%), S3n(7,59%), S3r,n(5,24%), N1r(12,84%), N1r,s/m(14,99%), N1r,e(1,63%), N2r (9,59%), N2s/m (12,45%) and N2s/m,e(0,9%); There are 12 subclass actual land suitability for peanut plant, those are: S3w,n(12,47%), S3w,r,n(8,61%), S3t,w,n (0,84%), N1r (7,70%), N1r,e(1,63%), N1r,s/m (20,77%) ,N2s/m(0,66%), N2w (19,79%), N2s/m,e(0,90%), N2w,r(2,51%), N2w,s/m(10.46%), and N2w,r,s/m(4,90%); (2) Potential land suitability for coffe plant with a medium management level produced eight land suitability subclass include: S2r,s/m, S2w,r,f,n, S2w,r,f,n,s/m, S3r,n; S3r,s/m, S3r,n,s/m, S3r,s/m,e and N1s/m; Potential land suitability for coffe plant with a high management level prodused nine land suitability subclass include S2s/m, S2w,r,f,n, S2w,r,f,n,s/m, S3s/m, S3r,n, S3n,s/m, S3 r,s/m, N1s/m and N1r,s/m; Potential land suitability for rubber plant with medium management level produced 7 subclass suitability include: S2t,w,n, S3r, S3t, S3w,r,n, S3t,w,r,n,s/m,e, N1s/m, N1r,s/m; and Potential land suitability for rubber plant with a high management level prodused six land suitability subclass include: S2t,n, S2w,r,n,s/m, S3t, S3w,r,n, S3t,w,n,s/m and N1s/m.(3) Highest productivity of coffe plants get on land suitability subclass N1r,s/m which is 896 kgs/Ha/year and have the lowest productivity of coffe plants get on land suitability subclass N2s/m is 47 kgs/Ha/year; Highest productivity of Rubber plants get on land suitability subclass S3w,n which is 2137 Kgs/Ha/year and have the lowest productivity of rubber plants get on land suitability subclass N2w,s/m is1618 kgs/Ha/year.Kata kunci : Kesesuaian Lahan, Daerah Aliran Sungai,Tanaman Kopi dan Karet